2003
DOI: 10.1042/bj20021891
|View full text |Cite
|
Sign up to set email alerts
|

Purification and identification of a binding protein for pancreatic secretory trypsin inhibitor: a novel role of the inhibitor as an anti-granzyme A

Abstract: Pancreatic secretory trypsin inhibitor (PSTI) is a potent trypsin inhibitor that is mainly found in pancreatic juice. PSTI has been shown to bind specifically to a protein, distinct from trypsin, on the surface of dispersed cells obtained from tissues such as small intestine. In the present study, we affinity-purified the binding protein from the 2% (w/v) Triton X-100-soluble fraction of dispersed rat small-intestinal cells using recombinant rat PSTI. Partial N-terminal sequencing of the purified protein gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Thus, rather than secreting a bacterial proteinase, C. rodentium infection in vivo induces host tissues to release PAR 2 -activating serine proteinases. Granzyme A and kallikrein B are both known to be inhibited by STI (36,37), and it is possible that the inhibition by STI of these proteinases could account for its antiinflammatory effects in vivo. It also needs to be recognized that human mesotrypsin (38) and trypsin IV (39) are not inhibited by STI, and, in fact, mesotrypsin degrades STI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rather than secreting a bacterial proteinase, C. rodentium infection in vivo induces host tissues to release PAR 2 -activating serine proteinases. Granzyme A and kallikrein B are both known to be inhibited by STI (36,37), and it is possible that the inhibition by STI of these proteinases could account for its antiinflammatory effects in vivo. It also needs to be recognized that human mesotrypsin (38) and trypsin IV (39) are not inhibited by STI, and, in fact, mesotrypsin degrades STI.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapancreatic or blood PSTI might regulate extracellular activity of GzmA. Unlike the other two GzmA inhibitors, PSTI inhibits GzmA complexed to proteoglycans (115). It is still not clear whether any of these GzmA inhibitors are expressed in cytotoxic lymphocytes.…”
Section: Gzma Endogenous Inhibitorsmentioning
confidence: 99%
“…Extracellular GzmA complexed to proteoglycans is resistant to these two protease inhibitors (114). A recent study identified another GzmA inhibitor, pancreatic secretory trypsin inhibitor (PSTI), from pancreatic secretions (115). PSTI is found in the blood, particularly in patients with severe inflammation and tissue destruction (116,117).…”
Section: Gzma Endogenous Inhibitorsmentioning
confidence: 99%
“…-charged resin (HisLink TM resin, Promega, Madison, WI, USA) were performed as described previously (Hirayasu et al 2005(Hirayasu et al , 2007(Hirayasu et al , 2008Tsuzuki et al 2003). In order to obtain the active form, the purified rGrA was incubated with 2.0 units/mL recombinant enterokinase (Novagen, Madison, WI, USA) for 18 h at 22°C.…”
Section: Methodsmentioning
confidence: 99%